Familial Hemophagocytic Lymphohistiocytosis Presenting as Hydrops Fetalis - Sota Iwatani; Kazuya Uemura; Masami Mizobuchi; Seiji Yoshimoto; Keiichiro Kawasaki; Yoshiyuki Kosaka; Masayuki Hori; Takahiro Yasumi; Hideto Nakao (Thieme Medical Publishers, Inc., 2015)
Abstract Background Familial hemophagocytic lymphohistiocytosis (FLH) is an autosomal recessive disorder of immune regulation that leads to a hyperinflammatory syndrome. Fetal onset FHL is extremely rare and is considered to be the most severe form of FHL. Case We report a preterm case of FHL that presented as hydrops fetalis. The infant was treated with a chemotherapy regimen based on the HLH-2004 protocol from the third day of life. However, he had persistent cytopenia and died on the 18th day of life due to bacteremia. The detection of defective perforin expression in the patient's natural killer cells and mutations in the PRF1 gene resulted in a molecular diagnosis of FHL. Conclusion We suggest that early diagnosis and the development of an appropriate immunosuppressive strategy that can induce and maintain remission until hematopoietic stem cell transplantation can be performed are required to improve the outcomes of fetal onset FHL.